Exploring the Link between ABO Blood Groups and Obesity among Young Adults - Shakil Ahmed Shaikh; Nazia Azam Yousfani; Muhammad Muqeem Mangi; Salma Farukh Memon; Keenjhar Rani Laghari; Arsalan Ahmed Uqaili (University of Lahore, 2024)
Objective: To explore the link between the ABO blood groups and obesity among young adults of Hyderabad district, Sind, Pakistan. Methods: This cross-sectional study was conducted from February 2021 to January 2022, and included 582 randomly selected participants, including 301  males and 281 females, aged between 18 to 40 years, from various institutions of district Hyderabad, including students, faculty members, and employee of universities, colleges, hospitals. A simple random sampling technique was used for the collection of data. Before induction, verbal consent was taken from all the participants. Data was collected by a self-structured questionnaire including sociodemographic characteristics. A brief history was taken relevant to the parameters of the study followed by measuring Body Mass Index, waist circumference, and waist-hip ratio. BMI was categorized with South Asian standards. Data collected through structured questionnaires and anthropometric parameters were analyzed by SPSS version 20.0. Results: In this study, the data of 582 participants were included out of 600 participants, as the remaining 18 could not provide complete data. The mean age in male participants was 27.83 ± 5.478 and in females was 22.27 ± 4.730. The average BMI in male participants was 25.81 ± 5.08 and in females was 24.00 ±4.90. Overall, 205 B blood group participants were found obese, which included 111 male participants and 94 female participants, followed by blood 197 group O participants, 130 A blood group participants, and 50 AB group individuals. In total, there were 536 Rh positives, and only 42 Rh negatives. Individuals with blood group B and Rh-positive status were identified at being greater risk of developing higher BMI, waist-hip ratio, and waist circumference. Conclusion: The evidence found in this study proved a positive association of the types of blood groups with BMI, waist-hip ratio, and waist circumference.